2021
DOI: 10.3390/cells10010178
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-Activating Enzyme Subunit 1 (SAE1) Is a Promising Diagnostic Cancer Metabolism Biomarker of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most diagnosed malignancies and a leading cause of cancer-related mortality globally. This is exacerbated by its highly aggressive phenotype, and limitation in early diagnosis and effective therapies. The SUMO-activating enzyme subunit 1 (SAE1) is a component of a heterodimeric small ubiquitin-related modifier that plays a vital role in SUMOylation, a post-translational modification involving in cellular events such as regulation of transcription, cell cycle and apo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…This indicates that the SUMOs protein plays an essential role in the development of HCC and suggests the potential of SUMOs as future targets. These data and Jiann’s research results are mutually corroborating, implying the potential of SUMOs as prognostic markers of HCC [ 48 ].…”
Section: The Expression and Clinical Significance Of Sumos Proteins In Hccsupporting
confidence: 60%
See 1 more Smart Citation
“…This indicates that the SUMOs protein plays an essential role in the development of HCC and suggests the potential of SUMOs as future targets. These data and Jiann’s research results are mutually corroborating, implying the potential of SUMOs as prognostic markers of HCC [ 48 ].…”
Section: The Expression and Clinical Significance Of Sumos Proteins In Hccsupporting
confidence: 60%
“…At present, there have been studies expounding the possible clinical applications of SUMOs protein. In the study of Jiann et al [ 48 ], it was found that the mRNA levels of SAE1 in liver cancer tumour tissues were significantly upregulated ( p < 0.0001). Patients with higher SAE1 mRNA have a worse disease survival rate (DSS) and progression-free survival rate (PFS).…”
Section: The Expression and Clinical Significance Of Sumos Proteins In Hccmentioning
confidence: 99%
“…SUMO is crucial for various types of cancer due to its reversible nature in cell cycle progression and genome integrity [ 34 ]. Apart from RANBP2, multiple SUMO enzymes are responsible for cancer progression and represent targetable cancer metabolic biomarkers [ 35 , 36 ]. In the current study, the immunofluorescence study indicated that CEBPα mostly resides in nuclei as a typical transcriptional factor.…”
Section: Discussionmentioning
confidence: 99%
“…SAE1 is a component of a heterodimeric small ubiquitin-related modifier that plays a vital role in SUMOylation, a post-translational modification involving in cellular events such as regulation of transcription, cell cycle and apoptosis. A recent study showed that SAE1 was overexpressed in HCC, and its overexpression was stage and grade-dependent and associated with poor survival 37 . TOP2A is one of the tumor drivers in a myriad of malignant tumors, and it increased cancer cell proliferation through inhibiting P53 activity 38 .…”
Section: Discussionmentioning
confidence: 99%